Deutsch-russische Musikbegegnungen 1: Studien - Weiss, Stefan (Georg Olms Verlag, 2021)
Between the fateful political years of 1917 and 1933, German and Russian musical cultures encountered each other in new and sometimes controversial constellations, which this volume explores in twelve detailed studies. From a German perspective, "Russian music" at the time could be identified in thought as much with the old tsarist empire as with the new socialist social order: in Berlin, the musical art of old Russia was heard in the concerts of fugitive performers as in the exile cabaret of the Blauer Vogel; at the same time, the "Society of Friends of New Russia" promoted sympathy for Soviet music there. In post-revolutionary Russia itself, the compositions of Paul Hindemith and Alban Berg received widespread attention, while the classicist Beethoven was stylized as a model for Soviet music. The volume follows emigrants such as Sergei Prokof'ev and Vladimir Šcerbacëv in their often astonished perceptions of the modern German music scene, examines music-economic as well as music-aesthetic entanglements, and also includes the complex history of mutual reception.